Implementasi Kebijakan Program Inovasi Pembangunan dan Pemberdayaan Kewilayahan (PIPPK) di Kecamatan Arcamanik Kota Bandung - Silviana Dewi; Atik Rochaeni; Dadan Kurnia (Universitas 17 Agustus 1945, 2024)
One of the efforts by the Bandung City Government to alleviate poverty is through the Regional Innovation and Empowerment Development Program (PIPPK). This program aims to promote equitable development in neighborhood units (RW), PKK groups, Karang Taruna, and Community Empowerment Institutions. In practice, the budget absorption in Arcamanik District has reached 85.02% overall. Preliminary observations indicate that the implementation of PIPPK in Arcamanik District is not yet optimal. The aim of this research is to analyze the implementation of PIPPK policies, the challenges faced, and the efforts made by Arcamanik District. The study uses Thomas B. Smith's policy implementation theory, which includes: 1) Legal Framework; 2) Implementing Organization; 3) Target Groups; and 4) Environmental Factors. The research employs a descriptive qualitative design suitable for the issues to be discussed, as well as the local context in which the study is conducted. Data collection is carried out through interviews, document analysis, and observations, all of which are recorded in field notes. The implementation of the Regional Innovation and Empowerment Development Program (PIPPK) in Arcamanik District faces significant challenges in legal understanding, organizational coordination, target group identification, and environmental conditions. The Arcamanik District Government has taken steps such as training, socialization, and improving coordination to address these challenges. However, ongoing evaluation and monitoring are necessary to ensure the program's maximum benefit and achievement of its goals.